The importance of group activities for quality of life of women in postmenopause - doi:10.5020/18061230.2011.p376 - Renata Aparecida Calazans Negrão; Ana Silvia Moccellin (Universidade de Fortaleza, 2012)
Objective: To assess the quality of life of postmenopausal women who participate in different activities groups for elderly. Methods: We selected 59 women, divided as follows: hydrotherapy group (n = 15), physical activity and bingo group (n = 15), and a control group (n = 29). Data collection was done through a questionnaire evaluating the Quality of Life (WHOQOL-Bref), the Blatt and Kupperman Menopausal Index and Geriatric Depression Scale (GDS). The assessments were conducted in two stages with an interval of two months between each one. Results: There was an improvement in quality of life of women participants in activities groups with respect to the control group, and in all domains of quality of life questionnaire, the control group had lower values. Significant differences occurred in the environment domain, in comparing the hydrotherapy group and physical activity/bingo groups, of which the latter showed better responses. Conclusion: The activities groups were positive for improving quality of life of postmenopausal women, emphasizing the importance of encouraging the practice of not only physical activities, but also those that stimulate the social and psychological profile of these women.